La creación de un ámbito público transnacional (primera parte) - de Maria y Campos, Camila Pastor (El Colegio de México, 2012)
At the beginning of the XXIst century, Lebanese migrants to Mexico City have a median income which is significantly higher than that of the Mexican population. I argue that this is the product of the history of their migration, and the institutions that they have developed during the XXth century; which configured a transnational field of public debates which spanned the Mashreq and the American Mahjar, what we could call a “migrant public sphere”. The migration began in the late XIXth century, when a diverse cross section of Lebanon’s population traveled to the Americas for a variety of reasons. Those with greater access to resources provided employment and credit for the majority of migrants. The relationships which were initially personal or based in a common village of origin were maintained throughout the XXth century through a variety of institutions generated by the migrants. The earliest of those were aid institutions organized by religious communities; which were followed many decades later by nationally defined social institutions. In the process, a social identity category was created and presented to Mexican society which brings outlier success stories and the middle class majority under the same national category of “Lebanese”. This allows their collective identity to be perceived as one of higher prestige by non-Lebanese Mexicans than the “Lebanese” middle class migrant and migrant descent majority would have otherwise enjoyed, and provides new avenues for social mobility.